2014
DOI: 10.1016/j.ccell.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog Signaling Restrains Bladder Cancer Progression by Eliciting Stromal Production of Urothelial Differentiation Factors

Abstract: Summary Hedgehog (Hh) pathway inhibitors are clinically effective in treatment of basal cell carcinoma and medulloblastoma, but fail therapeutically or even accelerate progression in treatment of endodermally-derived colon and pancreatic cancers. In bladder, another organ of endodermal origin, we find that despite its initial presence in the cancer cell of origin Sonic hedgehog (Shh) expression is invariably lost during progression to invasive urothelial carcinoma. Genetic blockade of stromal response to Shh f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
185
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 172 publications
(208 citation statements)
references
References 51 publications
14
185
3
Order By: Relevance
“…Hence, the beneficial effects of Hh-mediated suppression of inflammation also extend to its downstream sequelae, namely progression to adenocarcinoma. Such effects of stromal Hh pathway activity have also been seen in epithelial tumor progression in the pancreas and bladder (10,14,31).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Hence, the beneficial effects of Hh-mediated suppression of inflammation also extend to its downstream sequelae, namely progression to adenocarcinoma. Such effects of stromal Hh pathway activity have also been seen in epithelial tumor progression in the pancreas and bladder (10,14,31).…”
Section: Discussionmentioning
confidence: 85%
“…1 B and C), which is not only a mediator but also a target of Hh signaling (5,9). Stromal ablation of Smo (in a Smo fl/fl background) thus can be accomplished using the stromally active Gli1 CreER driver (10) in the presence of tamoxifen to activate CreER recombinase. Indeed, tamoxifen treatment of Gli1 CreER/+ ;Smo fl/fl mice produced a 4.5-fold reduction in Gli1 transcript levels by quantitative RT-PCR (qRT-PCR) analysis compared with Gli1 CreER/+ ;Smo flox/+ control mice (Fig.…”
Section: Reduction Of Hh Pathway Activity Exacerbates Acute Dss-inducedmentioning
confidence: 99%
“…Previous studies have reported that the Hh signaling pathway participates in various tumor processes, including formation, development, metastasis and angiogenesis (38)(39)(40). In the present study, the expression of the molecules involved in the Hh signaling pathway was investigated, and the results revealed that GLI1, PTCH1, SMO and SHh were overexpressed in cervical cancer tissues (squamous carcinoma vs. normal cervical tissue, all P<0.01; adenocarcinoma vs. normal cervical tissue, P=0.014, P=0.007, P=0.007 and P=0.007, respectively).…”
Section: A B C D E F G Hmentioning
confidence: 99%
“…The concept of stromal Hh signalling showing tumour suppressive traits is not fully unprecedented as similar findings have been made in mouse models of bladder, prostate and colon cancer 31–33. In bladder cancer, for instance, Hh-activated stroma delivers pro-differentiating bone morphogenetic protein factors, thereby facilitating urothelial differentiation and interfering with carcinogenesis 31. It will be interesting to learn whether the tumour-suppressive functions of Hh signalling occur exclusively at certain tumour stages or whether they represent a general feature, applying to late as well as early stages.…”
Section: Introductionmentioning
confidence: 99%